Imaging Patterns of Cardiovascular Involvement in Mixed Connective Tissue Disease Evaluated by Cardiovascular Magnetic Resonance - Mavrogeni, Sophie; P. Sfikakis, Petros; Dimitroulas, Theodoros; Koutsogeorgopoulou, Loukia; Karabela, Georgia; Katsifis, Gikas; Stavropoulos, Efthymios; Gialafos, Elias; Spiliotis, George; Kolovou, Genovefa; D. Kitas, George (Inflammation & Allergy-Drug Targets (Discontinued), 2015)
Background: To clarify the imaging patterns of cardiovascular lesions in patients with mixed connective tissue disease (MCTD) and cardiovascular symptoms with or/ without abnormal routine non-invasive evaluation. Patients-Methods: Twenty-two MCTD patients (19F/3M), aged 38±4 yrs with cardiovascular symptoms were evaluated using a 1.5 T scanner. Of them, 8/22 had systemic lupus erythematosus (SLE), 5/22 rheumatoid arthritis (RA), 5/22 scleroderma (SSc) and 4/22 myositis (MY) overlap syndromes; 10/22 patients with MCTD presented with Raynaud phenomenon (RP) and all were positive for Anti-RNP antibodies. The cardiovascular magnetic resonance study (CMR) included evaluation of function, inflammation and fibrosis. Myocardial stress perfusion-fibrosis evaluation was performed only in MCTD patients with RP. Results: A positive CMR study was identified in 4/8 with SLE, 1/5 with RA, 4/5 with SSc and in 1/4 with MY like MCTD. The CMR lesions were subendocardial or transmural LGE following the distribution of coronary arteries, intramyocardial LGE and diffuse subendocardial LGE in SLE-RA, MY and SSc like MCTD, respectively. Although no evidence of fibrosis was identified in patients with RP, adenosine stress myocardial perfusion revealed diffuse subendocardial perfusion defects. No correlation between disease duration and/or inflammatory indices and cardiac lesions was identified. Conclusion: CMR can reveal myocardial lesions in MCTD patients with cardiac symptoms including myocardial infarction, inflammation, diffuse subendocardial fibrosis and diffuse perfusion defects, necessitating further cardiac investigation and/or treatment.
Keywords: Mixed connective tissue diseases